Improvement of vitamin A content of puto using squash - Iyo, Kashmir G.
ABSTRACT The objective of this study was to develop a puto with increased vitamin A content by the addition of squash. Preliminary studies showed that the optimum steaming time for 1 cm-thick squash pieces cooked in a 14.5-inch diameter and 4.5-inch depth steamer was 10 minutes. Consumer evaluation test results showed that substituting 38% of the amount of flour and milk with squash in puto was the optimum product formulation. Based on the sensory, physico-chemical and microbiological analyses, the product was reproducible using the puto-making procedure with established specifications. Based on vitamin analyses, the chosen formulation for the squash puto was almost twice as high in total vitamin A content compared to puto without squash.